Ministry of Trade and Industry Decree No. 784 of the Year 2010 On Amending Certain Provisions of The Regulations Of The Rules Enforcing The Provisions Of Law On Import And Export And The System Of Imported And Exported Goods Inspection And Control Procedures = وزارة التجارة والصناعة قرار رقم 784 لسنة 2010 بتعديل بعض أحكام لائحة القواعد المنفذة لأحكام قانون الاستيراد والتصدير ونظام إجراءات فحص ورقابة السلع المستوردة والمصدرة - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.